Impact of parental marital status on self-harm in Chinese primary school students: the mediating role of depression and the moderating effect of classmate relationships - Ming Ai; Xiao-Ming Xu; Wo Wang; JianMei Chen; Jinglan He; Qi Zhang; Su Hong; Yao Gan; Jun Cao; Daqin Ding; Jinhui Hu; Shuang Zhang; et al. (PeerJ)
Background Self-harm is an increasing global public health concern, with a growing prevalence in younger children. This study investigates the associations between parental marital status and self-harm behaviors among primary school students, with a focus on the mediating role of depressive symptoms and the moderating effect of classmate relationships. Methods A cross-sectional survey was conducted among 33,285 students (grades 3–6; mean age = 10.36 years) in the Shapingba District of Chongqing, China, from September to December 2020. Self-report measures included the Children’s Depression Inventory (CDI), general demographic data, self-harm behaviors, and parental marital status. Data were analyzed using SPSS 26.0 for descriptive statistics and Mplus 8.1 for structural equation modeling (SEM), assessing the effects of parental marital status on self-harm. Results The reporting rates of depression and self-harm in grades 3–6 of primary school are 16.3% and 12.7%, respectively. Parental separation exhibited a more pronounced overall impact on self-harm (β = 0.120) compared to divorce (β = 0.105). Positive classmate relationships mitigated the indirect effect of separation on self-harm mediated by depression, reducing it from 0.098 to 0.072. Additionally, these relationships attenuated the direct effect of divorce on self-harm, decreasing it from 0.088 to 0.043. Depression significantly mediates the relationship between parental separation and children’s self-harm, with direct and indirect effects accounting for 53% (β = 0.057) and 47% (β = 0.063) of the total effect, respectively. Conclusion The marital status of parents, especially in cases of separation, has a significant impact on self-harm behaviors among primary school students, with depression acting as a key mediating factor. Supportive classmate relationships can alleviate this effect, highlighting their importance in mental health interventions. These findings offer valuable insights for the development of policies aimed at reducing self-harm and enhancing psychological well-being among children.